Comparison of light and dark nitrogenase activity in selected soil cyanobacteria - Hrouzek, P; Lukesová, A; Simek, M (Folia microbiologica, 2004)
Frequency of heterocytes and nitrogenase activity (NA) under light and dark cultivation conditions was determined in 12 cyanobacterial strains isolated from various soil habitats. In spite of a high variability, significant differences in NA among the strains were found in response of light and dark cultivation. Relatively high NA (9.9-15.3 micromol/h C2H4 per g fresh mass) under light conditions and basal NA after 12 h of dark cultivation were detected in Anabaena, Nodularia, Tolypothrix, and 1 of Cylindrospermum strains. On the other hand, significantly lower NA (0.76-5.4 micromol/h C2H4 per g fresh mass) was found under light conditions in Trichormus, Nostoc and another Cylindrospermum strain; the activity completely disappeared after 12 h of dark cultivation. NA values were not directly related to the frequency of the heterocytes. The total NA of cyanobacterial colony was found to be probably independent of the number and/or position of heterocytes. Remarkable differences in NA between strains isolated from cultivated fields and strains originating from natural or non-cultivated soils were found.
Keywords: Darkness; Cyanobacteria; tma; světlo; Soil Microbiology; půdní mikrobiologie; Nitrogenase; sinice; Light; nitrogenasa